Design and build an underwater fishing light based on internet of thing - Nugraha, I Made Aditya; Ngurah Desnanjaya, I Gusti Made (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The utilization of fishing gear has been growing until now. One of these tools is an underwater fishing light that has been used by fishermen. However, until now this device still works conventionally and only provides one color. Based on these problems and the rapid development of the internet of things (IoT), an underwater fishing light was created and designed that can work with the IoT system and provide various colors of light according to the needs of fishermen. The design of this tool uses several tools and materials, such as generators, power adapters, controller modules, generators, and the Magic Home Pro application. This tool operates at 12 V DC and consumes 144 W of electric power. Utilization of this tool can also indirectly reduce the consumption of electrical and fuel energy on board and support the blue economy. The results of testing the device show that the IoT system can work well, provide light colors according to orders, is waterproof, and provides a fairly good light intensity with an average of 6.89 Lux (0-8 Lux).